SEAGRASS MEADOWS CONDITIONS IN PANTAR STRAIT AND SURROUNDING AREA, ALOR REGENCY, EAST NUSA TENGGARA - Lumban N. L. Toruan; Jahved Ferianto Maro; Ismawan Tallo (Universitas Nusa Cendana, 2020)
Abstract - Monitoring seagrass beds play an important role in the management of the coastal environment because of two things, that this activity is a method for improved management practices and can provide information about the status and condition of seagrass meadows, so it can be used as one consideration of adaptive management of marine protected areas. Data were collected in December 2016 in the northern part of Alor Island, namely Alila Beach, Mali Beach, Deere Beach, and Lapang Beach. Percentage of seagrass cover, pH, salinity, and temperature were measured in situ, while sediment organic content was analyzed in the laboratory using LOI method. The results showed a range of seagrass cover between 25,1-72,8% (x = 47,6 ± 17,5), pH 8,29-8,58 (x = 8,48 ± 0,10), salinity 31- 33 ppt (x = 31,7 ± 1,1), temperature 28,6-33,50C (x = 32,2 ± 1,9), and organic sediment content from 2,73 to 4,46% (x = 3,57 ± 0,76). There were six seagrasses composed of T. hemprichii, E. acoroides, C. rotundata, H. pinifolia, S. isoetifolium, and H. ovalis. Based on the condition of seagrass cover, the seagrass ecosystem in Pantar Strait and its surroundings were in a rare to the dense category, with criteria for the status of seagrass beds were poor (25,1%) to rich/healthy (72,8%) conditions. Keyword: Pantar, Seagrass, Mangrove, Sea Urchin, Sea Cucumber Abstrak - Kegiatan monitoring padang lamun berperan penting dalam pengelolaan lingkungan pesisir karena dua hal, yaitu kegiatan ini merupakan suatu metode untuk peningkatan praktik pengelolaan dan dapat menyediakan informasi mengenai status dan kondisi padang lamun sehingga dapat digunakan sebagai salah satu pertimbangan adaptif pengelolaan kawasan perlindungan laut. Pengambilan data dilakukan pada Bulan Desember 2016 di bagian utara Pulau Alor, yaitu di Pantai Alila, Pantai Mali, Pantai Deere, dan Pantai Lapang. Data yang diukur secara insitu adalah persentase tutupan lamun, pH, salinitas, suhu, sementara kandungan organik sedimen dianalisis menggunakan metode pembakaran di laboratorium. Hasil kajian menunjukkan kisaran tutupan lamun antara 25,1-72,8% (x = 47,6±17,5), pH 8,29-8,58 (x = 8,48±0,10), salinitas 31-33 ppt (x = 31,7±1,1), suhu 28,6-33,50C (x = 32,2±1,9), dan kandungan organik sedimen 2,73-4,46 % (x = 3,57±0,76). Terdapat enam jenis lamun, yaitu T. hemprichii, E. acoroides, C. rotundata, H. pinifolia, S. isoetifolium, dan H. ovalis. Berdasarkan kondisi tutupan lamun, maka ekosistem lamun di Selat Pantar dan sekitarnya berada pada kategori jarang sampai padat, dengan kriteria status padang lamun berada pada kondisi miskin (25,1%) sampai kaya/sehat (72,8%). Kata Kunci: Pantar, Lamun, Mangrove, Bulu Babi, Teripang